Formation of Rural Territory: Peasants and their Persistence. A Case from the Southern Border of Mexico (2020)
This paper aims to introduce the reader to a historical perspective on the formation process of the rural territory along the Hondo River bank, in the southern border of Mexico, during the seventies. It also discusses the direct relationship between land tenure and the socio-territorial dynamics of the Mexican peasantry. For this, Marx’s theory of peasant economy and Chayanov’s theory of pre-capitalist societies are used to explain the symbiosis in territorybuilding. The method employed is desk research based on historical references, which allows analyzing different categories systematically, such as territoriality in the peasantry and peasant persistence within capitalism. This results in the question: Does capitalism promote the disappearance of peasants or contribute to their persistence?